Influence of antimicrobial photodynamic therapy as an adjunctive to scaling and root planing on alveolar bone loss: A systematic review and meta-analysis of animal studies - Alberton Nuernberg, Marta Aparecida [UNESP]; Janjacomo Miessi, Daniela Maria [UNESP]; Ivanaga, Camila Ayumi [UNESP]; Bocalon Olivo, Mariane [UNESP]; Ervolino, Edilson [UNESP]; Gouveia Garcia, Valdir [UNESP]; Wainwright, Mark; Theodoro, Letícia Helena [UNESP] (Elsevier, 2019)
Background: The study aimed to evaluate the effect of antimicrobial photodynamic therapy (aPDT) as adjunctive therapy to scaling and root planing in experimental periodontitis in rats, with or without systemic involvement, by means of histometric analysis of the furcation region. Methods: Systematic search was done using PubMed/MEDLINE, SCOPUS, EMBASE and ProQuest databases. Quantitative analysis of alveolar bone loss, with subcategories for the experimental periods studied, was performed. The analysis was performed through the mean difference (MD), with 95% confidence intervals (CIs) and according to SYRCLE guidelines. Results: Nine studies were considered eligible. A statistically favorable difference was observed for the use of aPDT in all periods studied in systemically healthy animals at 7 (P < 0.00001; MD: −0.71; 95% CI: [−0.85, −0.58]; I2: 90%), 15 (P < 0.00001; MD: −0.49; 95% CI: [−0.62, −0.37]; I2: 88%), and 30 (P < 0.00001; MD: −0.53; 95% CI: [−0.65, −0.41]; I2: 80%) days postoperatively. The difference was also observed for modified animals at 7 (P < 0.00001; MD: −1.03; 95% CI: [−1.43, −0.62]; I2: 97%), 15 (P < 0.00001; MD: −1.04; 95% CI: [−1.62, −0.46]; I2: 99%), and 30 (P < 0.00001; MD: −0.88; 95% CI: [−1.37, −0.39]; I2: 97%) days postoperatively. Conclusion: The adjunctive use of aPDT favored the reduction of alveolar bone loss in experimental periodontitis in rats, and this result was more evident in systemically compromised rats.
Keywords: Alveolar bone loss; Periodontal disease; Photochemotherapy; Systematic review